+0  
 
0
100
2
avatar+57 

Given that f(x) = 5x − 10 and g(x) = x + 3, solve for f(g(x)) when x = −1

also, please explain how to do other questions like this

 Jun 1, 2020
 #2
avatar+277 
+1

Given that f(x) = 5x − 10 and g(x) = x + 3, solve for f(g(x)) when x = −1

 

f(x) = 5x − 10

g(x) = x + 3

 

To solve for f(g(x)), write f(x) = x + 3 and set it equal to 5x - 10 like so:

f(x + 3) = 5x - 10

Now substitute x+3 on the right side in place of x. It should look something like this:

f(x + 3) = 5(x + 3) - 10

f(x + 3) = 5x + 15 - 10

f(x + 3) = 5x + 5

 

Substitute the value of -1 into x.

f(x + 3) = 5(-1) + 5

f(x + 3) = -5 +5

f(x + 3) = 0

 

f(g(x)) = 0

 Jun 1, 2020

23 Online Users

avatar
avatar
avatar
avatar